THE EFFECT OF THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE PRINCIPLES ON EMPLOYEES’ PERFORMANCE AT PERUMDA AIR MINUM MAKASSAR - Ismail Ismail; Syamsu Alam; Musran Munizu (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This research is aimed at examining and analyzing the effect of the implementation of the principles of Good Corporate Governance (GCG) on the employees’ performance at the drinking water regional company Makassar. Data of the research was collected by distributing questionnaires to 98 employees. Data was then analyzed by using Pearson Product Moment coefficient correlation to examine the positive effect of the principles of transparency, accountability, responsibility, independence, and fairness towards the employees’ performance. The results of the research indicated that all they have a significant effect on the employees’ performance. However, based on the results of the study obtained that the five variables of GCG namely transparency, accountability, responsibility, independence, and fairness do not have an influence simultaneously with the performance of employees in Perumda Air Minum Makassar. This is because one of the principles, namely responsibility does not affect the performance of employees in Perumda Air Minum Makassar (simultaneously) with the performance of employees in Perumda Air Minum Makassar.